Patient‐reported outcomes from KATHERINE: A phase 3 study of adjuvant trastuzumab emtansine versus trastuzumab in patients with residual invasive disease after neoadjuvant therapy for human epidermal growth factor receptor 2–positive breast cancer. Issue 13 (14th April 2020) - Conte, PierFranco; Schneeweiss, Andreas; Loibl, Sibylle; Mamounas, Eleftherios P.; von Minckwitz, Gunter; Mano, Max S.; Untch, Michael; Huang, Chiun‐Sheng; Wolmark, Norman; Rastogi, Priya; D'Hondt, Veronique; Redondo, Andrés; et al.
Abstract : Background: The phase 3 KATHERINE trial demonstrated significantly improved invasive disease–free survival with adjuvant trastuzumab emtansine (T‐DM1) versus trastuzumab in patients with HER2‐positive early breast cancer and residual invasive disease after neoadjuvant chemotherapy plus HER2‐targeted therapy. Methods: Patients who received taxane‐ and trastuzumab‐containing neoadjuvant therapy (with/without anthracyclines) and had residual invasive disease (breast and/or axillary nodes) at surgery were randomly assigned to 14 cycles of adjuvant T‐DM1 (3.6 mg/kg intravenously every 3 weeks) or trastuzumab (6 mg/kg intravenously every 3 weeks). The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–Core 30 (QLQ‐C30) and breast cancer module (QLQ‐BR23) were completed at screening, at day 1 of cycles 5 and 11, within 30 days after study drug completion, and at 6‐ and 12‐month follow‐up visits. Results: Of patients who were randomly assigned to T‐DM1 (n = 743) and trastuzumab (n = 743), 612 (82%) and 640 (86%), respectively, had valid baseline and ≥1 postbaseline assessments. No clinically meaningful changes (≥10 points) from baseline in mean QLQ‐C30 and QLQ‐BR23 scores occurred in either arm. More patients receiving T‐DM1 reported clinically meaningful deterioration at any assessment point in role functioning (49% vs 41%), appetite loss (38% vs 28%), constipation (47% vs 38%), fatigue (66% vs 60%), nausea/vomiting (39% vs 30%), and systemic therapy side effects (49% vs 36%). These differences were no longer apparent at the 6‐month follow‐up assessment, except for role functioning (23% vs 16%). Conclusion: These data suggest that health‐related quality of life was generally maintained in both study arms over the course of treatment. Abstract : Patient‐reported outcomes are reported from the randomized, phase 3 KATHERINE trial, which demonstrated significantly improved invasive disease–free survival with adjuvant T‐DM1 compared with trastuzumab in patients who had residual invasive disease following neoadjuvant chemotherapy plus HER2‐targeted therapy. Patients who are treated with T‐DM1 have a greater incidence of any grade and grade ≥3 adverse events compared with trastuzumab‐treated patients; however, these adverse events appear to have a minimal impact on patient‐reported quality of life.